FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PETANI PADI SAWAH DI DESA KOTO ARO KECAMATAN SIULAK KABUPATEN KERINCI - Mira Hastin (Jurnal Akrab Juara, 2018)
The purpose of this research is to analyze the influence of land area, farming cost and the amount of paddy production to paddy farmer income in Koto Aro village, Siulak Subdistrict, Kerinci Regency. Using stratified random sampling obtained sample of 30 farmers. Primary data in the form of questionnaires in the form of questionnaires distributed to respondents. The analysis technique used is descriptive and inductive which includes prerequisite test and hypothesis test with a significant level of 0.05. Methods of data analysis using multiple linear regression analysis. The results of this study indicate that the simultaneous land area, farming costs and the amount of paddy field production have a significant effect on farmer's income. And partially land area sdan rice production amount and have a positive and significant impact on farmers' income. While variable of farming cost have positive effect not significant to farmer income. Keywords: Land Area, Farm Business Cost, Total Production, Income